A simple molecular structure of ortho-derived perylene diimide diploid for non-fullerene organic solar cells with efficiency over 8%. Issue 42 (20th October 2017) - Wang, Helin; Chen, Lingcheng; Xiao, Yi
Abstract : A simple molecular structure of ortho -derived perylene diimides (PDI) diploid has been developed for non-fullerene organic solar cells (OSCs) with a high power conversion efficiency (PCE) of 8.3%, indicating that such a concise molecular structure with a high PCE has great potential for the practical applications in OSCs. Abstract : A simple molecular structure of ortho -derived perylene diimide (PDI ) diploid ( oo -2PDI ), aPDI derivative, as well as two bay -derivedPDI diploids ( bb -2PDI and bo -2PDI ), was designed and efficiently synthesized by efficient Ullmann coupling reactions. The photophysical and electrochemical properties indicate that oo -2PDI exhibits much stronger absorption than bb -2PDI in the visible region and a slightly higher lowest unoccupied molecular orbital (LUMO) level, which are beneficial for harvesting much sunlight and improving open circuit voltage in the organic solar cell (OSC) devices. On usingPTB7-Th with appropriate energy level alignment and well matched absorption as the electron donor, the active layer ofPTB7-Th : oo -2PDI exhibits a favorable morphology, higher carrier mobilities and more balanced carrier transport. As a result, the device based onPTB7-Th : oo -2PDI shows a power conversion efficiency (PCE) as high as 8.30% and a high short circuit current ( J SC ) of 18.79 mA cm −2, which are much higher than those of the other twoPDI diploids ( bb -2PDI and bo -2PDI ), highlighting the potential of ortho -derivedPDI diploid to realize high efficiency non-fullerene OSCs. Such a concise molecular structure and the high efficiency make this compound promising for practical applications in OSCs.